Composite oxide-coated barium titanate dielectric powder, preparation method, ceramic slurry and multilayer ceramic capacitor

CN123026440APending Publication Date: 2026-11-03BATTFLEX (WUHAN) TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611095348.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing technologies struggle to achieve uniform dispersion and stability of ceramic dielectric powder particles at the submicron and nanoscale in multilayer ceramic capacitors. Furthermore, sintering in a reducing atmosphere can easily lead to the reduction of dielectric powder, resulting in decreased resistivity. In addition, uneven distribution of additives in traditional processes can cause abnormal grain growth and a decrease in insulation resistance reliability.

Method used

A composite oxide nanolayer composed of oxides of calcium (Ca), zirconium (Zr), and manganese (Mn) was constructed on the surface of barium titanate dielectric powder using atomic layer deposition (ALD) technology. This formed a dense Ca-Zr-Mn-O nanolayer, which improved dispersion stability and grain growth under reducing atmosphere through atomic-level uniform distribution. Through the synergistic effect of Ca, Zr, and Mn, surface chemical stability, outer layer control of grains, and improved reliability of reducing atmosphere were achieved simultaneously.

Benefits of technology

This invention achieves temperature characteristics of multilayer ceramic capacitor dielectric powder, solving the problems in existing technologies. It enables efficient and economical sintering under a reducing atmosphere, suppressing Ba2+ dissolution and pH drift, improving dispersion stability, reducing abnormal grain growth and insulation resistance reliability, and enhancing the uniformity of the dielectric layer and the insulation resistance retention rate under high temperature and high humidity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure VPW5K6CBRVLSNTXDQHBTH8HPUZRXOT35BHCAJZR7
    Figure VPW5K6CBRVLSNTXDQHBTH8HPUZRXOT35BHCAJZR7
Patent Text Reader

Abstract

The application discloses a composite oxide coated barium titanate dielectric powder, a preparation method, ceramic slurry and a multilayer ceramic capacitor. The coated barium titanate dielectric powder comprises a barium titanate dielectric powder core and a composite oxide nanolayer on the surface of the barium titanate dielectric powder core. The barium titanate dielectric powder core comprises BaTiO3 or a barium titanate-based dielectric powder with BaTiO3 as a main crystal phase. The composite oxide nanolayer contains calcium, zirconium and manganese elements and is formed by powder atomic layer deposition. The composite oxide nanolayer can reduce Ba 2+ dissolution and pH drift, improve dispersion stability, and transform into Ca-Zr-Mn enriched grain boundary or shell layer regions during co-firing in a reducing atmosphere, thereby inhibiting abnormal grain growth, reducing oxygen vacancy related insulation degradation and improving high temperature and high humidity bias reliability of thin dielectric layer MLCC.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of electronic ceramic materials, surface modification of dielectric powders, and manufacturing technology of multilayer ceramic capacitors, specifically to a composite oxide-coated barium titanate dielectric powder, its preparation method, ceramic slurry, and multilayer ceramic capacitor. Background Technology

[0002] Multilayer ceramic capacitors are typically formed by alternating layers of ceramic dielectric paste and metal internal electrode paste using sheet forming, printing, or similar techniques, followed by co-sintering. As electronic products move towards miniaturization, higher capacitance, higher reliability, and automotive-grade applications, the thickness of multilayer ceramic capacitors is continuously decreasing, and the particle size of ceramic dielectric powder is gradually expanding towards submicron and nanoscale.

[0003] Ceramic dielectric powders typically have BaTiO3 as the main crystalline phase, but may also contain barium titanate-based solid solutions such as (Ba,Ca)TiO3, Ba(Ti,Zr)O3, Ba(Ti,Hf)O3, Ba(Ti,Sn)O3, or (Ba,Ca)(Ti,Zr)O3. In this specification, these powders are collectively referred to as BT-based dielectric powders, which readily exhibit surface Ba... 2+ Problems such as dissolution, pH drift, increased dispersant consumption, viscosity increase over time, and local agglomeration can affect the uniformity of cast films and the control of defects in ultrathin dielectric layers.

[0004] On the other hand, ceramic dielectric powder in Ni or Cu co-fired systems typically requires sintering in a reducing atmosphere followed by re-oxidation. Sintering in a reducing atmosphere leads to the reduction of the ceramic dielectric powder, thereby reducing resistivity. Multilayer ceramic chip capacitors using non-reducible dielectric materials have been proposed, but these devices generally have shorter insulation resistance (IR) lifetimes and lower reliability.

[0005] Traditional processes often involve wet mixing of additives such as Mg, Mn, rare earth elements, Zr, Ca, Si, B, or Li to adjust the grain boundaries, core-shell structure, and sintering behavior of dielectric ceramics. However, the distribution of these additives is affected by variations in mixing uniformity, particle size, and wet adsorption behavior, which can easily lead to localized compositional shifts under ultrathin dielectric layer conditions. If the surface composition of the ceramic dielectric powder and the distribution of additives are uneven, problems such as abnormal grain growth, uneven shell formation, oxygen vacancy-related insulation degradation, and decreased insulation resistance reliability under high-temperature, high-humidity, and bias conditions can easily occur.

[0006] Existing technologies have attempted to form metal oxide layers on the surface of BaTiO3 particles using liquid phase coating or aqueous deposition methods to improve dispersibility or introduce media additives. However, liquid phase coating is easily affected by pH, ionic strength, hydrolysis rate, drying agglomeration and residual ions, making it difficult to obtain sub-nanometer (2nm) continuous and compositionally controllable composite interface layers on the surface of ceramic media powders ranging from 50 to 300nm.

[0007] Atomic layer deposition (ALD) possesses self-limiting surface reaction characteristics, theoretically enabling the formation of nanolayers with controllable thickness on complex powder surfaces. However, for multilayer ceramic capacitor (MLCC) dielectric powders, simply depositing a single layer such as TiO2, Al2O3, SiO2, LiF, or B2O3 on the BaTiO3 surface cannot adequately address the synergistic issues of dispersion stability, grain growth control, reducing atmosphere reliability, and dielectric temperature characteristics required for thin dielectric layers. Therefore, a BT-based dielectric powder surface composite ALD modification scheme, distinct from single TiO2 dispersion stabilizing layers, single Al2O3 / SiO2 sintering-resistant layers, and LiF / B2O3 low-temperature sintering aids, is still needed. Summary of the Invention

[0008] To address the shortcomings of existing technologies, the first objective of this invention is to provide a barium titanate dielectric powder coated with a composite oxide, comprising a barium titanate dielectric powder core and a composite oxide nanolayer located on the surface of the barium titanate dielectric powder core; the barium titanate dielectric powder core comprises BaTiO3 or a barium titanate-based dielectric powder with BaTiO3 as the main crystalline phase; the composite oxide nanolayer is mainly composed of oxides of calcium (Ca), zirconium (Zr), and manganese (Mn), and the composite oxide nanolayer is formed by atomic layer deposition (ALD) process, wherein the Ca, Zr, and Mn elements are atomically uniformly distributed in the composite oxide nanolayer.

[0009] Furthermore, the average particle size of the barium titanate dielectric powder core is 50-300 nm, and the specific surface area is 2-30 m². 2 / g; the equivalent thickness of the composite oxide nanolayer is 0.4-1.6nm.

[0010] Furthermore, in the composite oxide nanolayer, the atomic ratio of Ca to Zr is 0.3:1 to 3:1, and the atomic percentage of Mn relative to the total amount of Ca, Zr and Mn is 0.5-12%.

[0011] Furthermore, the core of the barium titanate dielectric powder is pure phase BaTiO3, or a barium titanate-based solid solution with BaTiO3 as the main crystalline phase and containing modifying elements; the modifying elements include one or more of Ca, Sr, Zr, Hf, Sn, Mg, Mn or rare earth elements.

[0012] Furthermore, the barium titanate dielectric powder core includes at least one of BaTiO3, (Ba,Ca)TiO3, Ba(Ti,Zr)O3, Ba(Ti,Hf)O3, Ba(Ti,Sn)O3 or (Ba,Ca)(Ti,Zr)O3, and the mass percentage content of the BaTiO3 main crystalline phase is not less than 80%.

[0013] Furthermore, the microstructure of the composite oxide nanolayer is selected from any of the following: (1) A nanolayered structure formed by alternating stacking of Ca-O sublayers, Zr-O sublayers and Mn-O sublayers; (2) The mixed layer structure in which Ca, Zr and Mn elements are uniformly distributed at the atomic level in the thickness direction; (3) A gradient layer structure with a concentration gradient, wherein the side closer to the core of the barium titanate dielectric powder is rich in Zr elements relative to the rest, and the side farther away from the core of the barium titanate dielectric powder is rich in Ca and Mn elements relative to the rest.

[0014] Furthermore, the composite oxide nanolayer is characterized in that it is a multi-element composite oxide phase, which does not contain a continuous single compound phase composed of Ti, Al, Si, Li, F or B elements; and based on the total number of atoms of the composite oxide nanolayer itself, the total atomic percentage of the six impurity elements Ti, Al, Si, Li, F and B is less than 10%.

[0015] Furthermore, after dispersing the coated barium titanate media powder in an aqueous medium with a pH of 6.5-7.5 to form a dispersion with a solid content of more than 50 wt%, and allowing it to stand at 25°C for 12 hours, the pH change of the dispersion is no greater than 0.5, and Ba dissolves... 2+ The concentration is lower than that of the comparative dispersion prepared using uncoated BT-based media powder, wherein the particle size distribution D90 / D10 of the coated barium titanate media powder after dispersion is not greater than 4.0, preferably not greater than 3.0.

[0016] The second objective of this invention is to provide a method for preparing barium titanate dielectric powder coated with composite oxide, using barium titanate dielectric powder as the core, and including the following steps: S1: The barium titanate dielectric powder is dried and surface activated; S2: Place the treated barium titanate dielectric powder into a powder atomic layer deposition reactor; S3: Perform a Zr-O deposition sub-cycle, including pulsed introduction of Zr source precursor into the reactor and purging, followed by pulsed introduction of oxygen source and purging; S4: Perform a Ca-O deposition sub-cycle, including pulsed introduction of Ca source precursor into the reactor and purging, followed by pulsed introduction of oxygen source and purging; S5: Perform a Mn-O deposition sub-cycle, including pulsed introduction of Mn source precursor into the reactor and purging, followed by pulsed introduction of oxygen source and purging; S6: Combining S3, S4 and S5 into a supercycle and repeating it to form the composite oxide nanolayer on the surface of barium titanate dielectric powder; Each supercycle includes 1-5 Zr-O deposition subcycles and 1-5 Ca-O deposition subcycles, and the ratio of the number of executions of the Zr-O deposition subcycle, Ca-O deposition subcycle and Mn-O deposition subcycle is (1-5):(1-5):(0.1-2); the powder atomic layer deposition temperature is 80-280℃.

[0017] Further, the Zr source precursor is tetra(dimethylamino)zirconium, tetra(diethylamino)zirconium, tetra(ethylmethylamino)zirconium, tert-butoxide zirconium, or a combination thereof; the Ca source precursor is bis(trimethylsilyl)aminocalcium, dicyclopentadienylcalcium, a calcium β-diketone complex, or a combination thereof; the Mn source precursor is dicyclopentadienylmanganese, tris(2,2,6,6-tetramethyl-3,5-heptadecanoic acid)manganese, a manganese amidine complex, or a combination thereof; and the oxygen source is H2O, O3, oxygen plasma, alcohol vapor, or a combination thereof.

[0018] Furthermore, the powder atomic layer deposition reactor is a vibrating fluidized bed reactor, a rotating bed reactor, a pulsed fluidized bed reactor, an acoustically assisted fluidized bed reactor, or a stirred bed reactor. During the deposition process, the agglomeration of barium titanate media powder is reduced by powder tumbling, vibration, pulsed airflow, acoustic assistance, or periodic vacuuming. The core of the barium titanate media powder is in a fluidized state or a tumbling and rotating state within the reactor.

[0019] A third objective of this invention is to provide a ceramic slurry comprising the aforementioned composite oxide-coated barium titanate media powder, an organic carrier, a dispersant, and a solvent. The solvent is an aqueous solvent or an alcohol-water mixture; the solid mass percentage of the barium titanate dielectric powder coated with the composite oxide in the ceramic slurry is 45-80 wt%, and the mass percentage of the dispersant relative to the barium titanate dielectric powder coated with the composite oxide is ≤2.0 wt%.

[0020] A fourth objective of the present invention is a multilayer ceramic capacitor, comprising a ceramic body and external electrodes disposed at both ends of the ceramic body; the ceramic body comprises a plurality of alternating dielectric layers and a plurality of internal electrode layers, characterized in that at least one of the dielectric layers is prepared by casting, drying, laminating, degreasing and sintering the ceramic slurry under a reducing atmosphere, and the internal electrode layers comprise at least one of Ni, Ni alloy, Cu or Cu alloy.

[0021] Furthermore, the sintered thickness of the dielectric layer is 0.3-2.0 μm, and the average grain size of the barium titanate-based grains in the dielectric layer is 0.10-0.35 μm; the barium titanate-based grains have an outer layer region enriched with Ca, Zr and Mn and a central region that maintains the main crystalline phase of barium titanate, and the thickness of the outer layer region is 5-40 nm.

[0022] The temperature characteristics of the multilayer ceramic capacitor provided by this invention meet the EIA standard X5R, X7R or X8R.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) Compared with uncoated BT-based media powder, the present invention constructs a dense Ca-Zr-Mn-O composite oxide nanolayer on the surface of BT powder through powder ALD, which effectively blocks the contact between water molecules and the BT core as a physical barrier and effectively inhibits Ba 2+ Dissolution and pH shift improve the dispersion stability of aqueous or alcohol-based slurries.

[0024] (2) Compared with a single TiO2 ALD layer, this invention does not simply form Ba through TiO2. 2+ Instead of a dissolution barrier, it achieves surface chemical stability, grain outer layer regulation, and improved reducing atmosphere reliability through the synergistic effect of Ca, Zr, and Mn. During co-firing in a reducing atmosphere, the Ca-Zr-Mn coating layer on the surface diffuses inward, transforming into Ca-Zr-Mn-enriched grain boundary or shell regions. The introduction of Ca and Zr effectively reduces grain boundary mobility, forming a uniform "core-shell" structure, which strongly inhibits abnormal grain growth in the thin dielectric layer. Mn, as a variable valence acceptor element, is enriched in the grain boundaries and shell, and its variable valence characteristics (Mn... 2+ / Mn 3 + / Mn 4+ It can effectively capture oxygen vacancies and free electrons, block the long-range migration of oxygen vacancies, and significantly reduce insulation degradation.

[0025] (3) Compared with a single Al2O3 sintering barrier layer, the composite layer of the present invention is more likely to be transformed into a Ca-Zr-Mn enriched outer layer or grain boundary region that is compatible with BT grains after co-firing, thereby reducing the risk of dielectric constant reduction caused by excessive residue of non-ferroelectric insulating phase.

[0026] (4) The powder ALD technology overcomes the defect of component segregation caused by traditional liquid / solid doping, ensuring that the modified elements are uniformly distributed at the atomic level on the surface of each nano-BT powder, and eliminating local micro-weak links in thin-layer MLCC.

[0027] (5) The MLCC dielectric layer prepared by the ceramic slurry of the present invention can improve the uniformity of grain size after sintering, suppress abnormal grain growth, reduce pores and local composition shift, and improve the insulation resistance retention rate under high temperature and high humidity bias. Detailed Implementation

[0028] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. The specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention.

[0029] In this specification, BT-based dielectric powder refers to barium titanate-based dielectric powder with BaTiO3 or BaTiO3 as the main crystalline phase and may contain one or more modifying elements selected from Ca, Sr, Zr, Hf, Sn, Mg, Mn or rare earth elements.

[0030] In this specification, the tetragonal c / a ratio is an indicator used to describe the degree of lattice stretching of a material crystal in a tetragonal crystal system. a: lattice constant of the unit cell in the x / y direction, c: lattice constant of the unit cell in the z direction. When c / a > 1, it indicates a more pronounced tetragonal distortion.

[0031] In this specification, equivalent thickness refers to the average film thickness calculated based on high-resolution transmission electron microscopy, scanning transmission electron microscopy energy spectrum line scan, X-ray photoelectron spectroscopy depth profile, inductively coupled plasma elemental content, and powder specific surface area. When there are differences in the values ​​measured by different methods, the average value calculated by high-resolution transmission electron microscopy and elemental content can be used as the equivalent thickness.

[0032] The performance data in the embodiments of this specification are predictive data based on material sintering behavior, film thickness, surface chemical stability, and MLCC dielectric layer process, used to illustrate the technical effects that the present invention can achieve.

[0033] Example 1: Preparation of Ca-Zr-Mn-O composite ALD-coated BaTiO3 media powder and slurry (1) Pretreatment of BaTiO3 dielectric powder core A D50 of approximately 120 nm and a specific surface area of ​​approximately 8.5 m² were selected. 2BaTiO3 powder with a tetragonal c / a ratio of not less than 1.008 was used as the core of the BT-based dielectric powder. D50 ≈ 120 nm is the ideal particle size for preparing ultrathin dielectric layers (<1 μm). The c / a ratio (tetragonality) ≥ 1.008 ensures the powder has an excellent tetragonal crystal structure, thus guaranteeing high dielectric constant and ferroelectricity. The powder was vacuum dried at 120℃ for 2 hours to remove physically adsorbed free water from the powder surface, preventing premature hydrolysis of the metal precursor during ALD (causing CVD side reactions) and disrupting the self-limiting properties of ALD. Surface activation treatment was then performed in nitrogen gas containing trace amounts of water vapor to increase surface reaction sites. The ALD reaction depends on surface hydroxyl groups (-OH). After drying, the number of surface hydroxyl groups decreased, and the trace water vapor treatment allowed for re-hydroxylation of the BaTiO3 surface, providing sufficient initial nucleation sites and eliminating the nucleation delay of ALD.

[0034] (2) Powder atomic layer deposition (ALD) coating The treated BaTiO3 powder was placed in a vibrating fluidized bed powder ALD reactor. The nanoparticles are prone to agglomeration, and ordinary fluidized beds are prone to channeling. Vibration can break up the soft agglomerates, make the powder uniformly fluidized, and ensure that the precursor gas is in full contact with the surface of each powder particle, achieving 100% shape-preserving coating.

[0035] The deposition temperature in the reaction chamber was set to 180°C, the base pressure in the reaction chamber was 0.1~1.0 Torr, and the carrier gas (N2) flow rate was 50-200 sccm. In this embodiment, the precursor sources were set as follows: tetrakis(dimethylamino)zirconium (TEMAZ) as the Zr source; and bis(trimethylsilyl)aminocalcium Ca(HMDS) as the Zr source. 2】 Alternatively, calcium β-diketone complexes can be used as the Ca source; dicyclopentadienyl manganese MnCp2 or manganese β-diketone complexes can be used as Mn precursors as the Mn source.

[0036] Among them, Zr doping can broaden the Curie peak and significantly improve the stability of dielectric temperature; Ca doping replaces Ba sites, which can effectively suppress abnormal grain growth during sintering, refine grains, and improve the ceramic's resistance to reduction and mechanical strength; Mn is a typical acceptor dopant that can capture oxygen vacancies generated during sintering in a reducing atmosphere, greatly reduce leakage current, and extend the high-temperature and high-load life by several times.

[0037] The deposition process is carried out in units of supercycles. One supercycle includes two Zr-O cycles, two Ca-O cycles, and one Mn-O cycle. By precisely controlling the proportion of subcycles, the stoichiometry of each element in the ternary composite oxide is adjusted at the atomic level to achieve synergistic effects of specific functions. The specific operation of the subcycles is as follows: Zr-O subcycle (repeated twice): pulse TEMAZ 1s, carrier gas purge 30s, pulse O 33s, carrier gas purge 30s; Ca-O sub-cycle (repeated twice): pulsed Ca source for 1s, carrier gas purging for 30s, pulsed O3 for 3s - carrier gas purging for 30s; Mn-O sub-cycle (repeated once): pulsed Mn source for 1s, carrier gas purge for 30s, pulsed O for 33s, carrier gas purge for 30s.

[0038] Among them, O3 plasma has a strong oxidizing ability, which can ensure that the variable valence element Mn is fully oxidized to the target valence state (Mn 2+ / Mn 3+ Furthermore, the gaseous oxygen source can prevent secondary agglomeration of powder caused by capillary forces of liquid water.

[0039] Four supercycles were performed to obtain BaTiO3 dielectric powder coated with a Ca-Zr-Mn-O composite oxide nanolayer. The equivalent thickness, calculated by ICP-OES, was approximately 0.8 nm. XPS analysis showed that the atomic ratio of Ca to Zr in the coating layer was approximately 1:1, and the atomic percentage of Mn relative to the total amount of Ca, Zr, and Mn was approximately 5%. STEM-EDS line scanning along the thickness direction revealed a uniform thickness distribution of the Ca-Zr-Mn-O composite oxide nanolayer.

[0040] Example 2: Gradient ALD-coated BT powder enriched on the inside of Zr and on the outside of Ca / Mn (1) Pretreatment of BaTiO3 dielectric powder core The D50 is selected to be approximately 90 nm, and the specific surface area is approximately 12 m². 2 BaTiO3 powder with a tetragonal phase c / a ratio of not less than 1.008 was used as the core of the BT-based media powder, and the pretreatment steps such as drying and activation were the same as in Example 1.

[0041] (2) Gradient powder atomic layer deposition (ALD) coating The activated BaTiO3 powder was placed in a vibrating fluidized bed powder ALD reactor. The reaction chamber temperature was set to 200℃, and the base pressure was 0.1-1.0 Torr. The precursor type and heating temperature were the same as in Example 1. In this example, a segmented deposition strategy was used to construct a gradient composite nanolayer. The specific steps are as follows: Deposition of the inner Zr enrichment layer: First, six consecutive Zr-O deposition cycles were performed (TDMAZ pulse 1s, carrier gas purging 30s; H2O pulse 3s, carrier gas purging 30s). Intermediate transition layer deposition: Subsequently, four supercycles were performed, each supercycle consisting of one Zr-O cycle, one Ca-O cycle, and one Mn-O cycle (the precursor pulses and purge times were the same as in Example 1). Deposition of the outer Ca / Mn enrichment layer: Finally, five consecutive Ca-O and three Mn-O deposition cycles were performed.

[0042] After deposition, a Ca-Zr-Mn-O gradient composite nanolayer with an equivalent thickness of about 1.1 nm was formed. STEM-EDS line scanning along the thickness direction revealed that the coating layer had obvious concentration gradient characteristics, with the side closer to the BT-based dielectric powder core being relatively rich in Zr, and the side farther away from the BT-based dielectric powder core being relatively rich in Ca and Mn.

[0043] Among them, ZrO2 has extremely high chemical stability and acid and alkali resistance. When the Zr-rich layer is tightly attached to the BT core, it can form the densest physical barrier the moment the powder comes into contact with the aqueous slurry, thus maximally suppressing the BaO2 degradation caused by the extremely high surface energy of the 90nm ultrafine powder. 2+ Vigorous dissolution; in the early stage of sintering, Zr 4+ (Ionic radius 0.072 nm) and Ti 4+ With a radius of 0.0605 nm, they can easily diffuse into the B site of the BT lattice to form a (Ba,Ca)(Ti,Zr)O3 solid solution. The incorporation of Zr will significantly reduce the surface energy and migration rate of the grain boundaries. The rich Zr content on the inner side ensures that in the most critical early stage of sintering densification, it is crucial to prevent catastrophic abnormal grain growth of the ultrathin dielectric layer during sintering.

[0044] Ca 2+ (A-site doping) and Mn (B-site or grain boundary segregation) are enriched on the outer side, and are more likely to diffuse towards grain boundaries and particle edges in the later stages of sintering. This promotes the formation of a typical ferroelectric core-paraelectric / weakly ferroelectric shell structure in BT particles. The internal stress effect generated by this core-shell structure can effectively broaden the curve of dielectric constant change with temperature, resulting in improved temperature stability of the dielectric constant. This is the microscopic basis for meeting the temperature characteristics of X5R / X7R (X5R and X7R are commonly used material codes in multilayer ceramic capacitors (MLCCs). X5R: operating temperature range -55℃ to +85℃, with a capacitance change rate not exceeding ±15% over the entire temperature range. X7R: operating temperature range -55℃ to +125℃, with a capacitance change rate not exceeding ±15% over the entire temperature range).

[0045] During sintering in a reducing atmosphere, oxygen vacancies are mainly generated and migrate in the grain boundary and shell regions, enriching the variable-valence element Mn on the outer side (i.e., the future grain boundary and shell regions), thus increasing the concentration of Mn ions (Mn... 2+ / Mn 3+ / Mn 4+ It can form traps in the region where oxygen vacancies are most concentrated and migration is most active. Compared with uniform distribution, Mn enriched on the outside can achieve more efficient oxygen vacancy pinning with less doping, thereby significantly reducing leakage current, improving high temperature and high humidity bias (THB) lifetime, and will not cause a decrease in dielectric constant due to excessive Mn.

[0046] There is a certain lattice mismatch between pure ZrO2 and the BT core, as well as between pure CaO / MnOx and ZrO2. An alternating 1:1:1 deposition transition layer is used in between to achieve a smooth transition of composition at the atomic scale. This alleviates the thermal stress and lattice distortion inside the cladding layer and between the cladding layer and the BT core, prevents the cladding layer from peeling off or generating microcracks during sintering and cooling, and ensures the structural integrity of the dielectric layer.

[0047] Example 3: Ca-Zr-Mn-O composite ALD-coated (Ba,Ca)(Ti,Zr)O3 dielectric powder (1) Pretreatment of (Ba,Ca)(Ti,Zr)O3 dielectric powder core (Ba,Ca)(Ti,Zr)O3 with a D50 of approximately 150 nm and a specific surface area of ​​8 m² was selected. 2 / g, the powder serves as the core of the BT-based media powder, wherein the mass percentage of the main crystalline phase of BaTiO3 is not less than 80%, and the pretreatment steps such as drying and surface activation are the same as in Example 1.

[0048] (2) Rotating bed powder atomic layer deposition (ALD) coating The activated powder was placed in a rotating bed powder ALD reactor. The reaction chamber temperature was set to 180°C, the reaction chamber base pressure was set to 0.5-2.0 Torr, and the reaction chamber rotation speed was set to 30 Rpm. In this embodiment, a 150 nm solid solution powder was used. The powder has slightly larger particles, higher density, and relatively better flowability. For this type of powder, the rotating bed, through the design of the rotating drum and internal lifting plates, can not only achieve uniform coating, but also avoid the problem of fine powder loss caused by high-speed airflow in the fluidized bed, thereby improving the powder yield.

[0049] Alternating deposition of Zr-O, Ca-O, and Mn-O sublayers, with the same precursor types and process parameters as in Example 1.

[0050] After deposition, a Ca-Zr-Mn-O composite oxide nanolayer with an equivalent thickness of approximately 1.2 nm is formed.

[0051] Example 4: Preparation of ceramic slurry and MLCC (1) Preparation of water-based ceramic slurry The ALD-coated BaTiO3 powder obtained in Example 2 was dispersed in an aqueous carrier, and less than 1.0 wt% of a polycarboxylic acid dispersant and an appropriate amount of binder were added. The polycarboxylic acid dispersant, through electrostatic repulsion and steric hindrance, ensured high dispersion of the coated powder in the aqueous system, making the aqueous system environmentally friendly and cost-effective. After ball milling, filtration, and degassing, a ceramic slurry was obtained. The solid content of the BT-based dielectric powder in the ceramic slurry was 55-75 wt%, and the dispersant content relative to the BT-based dielectric powder was 0.3-1.5 wt%. This slurry is suitable for casting to form dielectric green sheets with a thickness of 0.8-1.5 μm.

[0052] In this embodiment, the aqueous carrier is deionized water, the polycarboxylic acid dispersant is ammonium polycarboxylate salt with an addition amount of 0.5-1.0 wt%, the binder is PVA with an addition amount of 3-5 wt%, the solid mass percentage of BT-based media powder coated in the ceramic slurry is 65 wt%, the addition amount of silicone defoamer is 0.1-0.3 wt%, and the pH adjuster is 10% ammonia water. The slurry is adjusted to pH 8.0-9.5.

[0053] (2) Fabrication of high-capacity thin dielectric layer MLCCs Using the gradient-coated BaTiO3 powder obtained in Example 2 as the main material, an aqueous ceramic slurry with a solid content of 65 wt% was prepared according to the above-mentioned aqueous slurry formulation and ball milling process.

[0054] The ceramic slurry is cast to form a dielectric green sheet with a thickness of 1.5 μm. A Ni inner electrode slurry with a thickness of 1.2 μm is printed on the dielectric green sheet. Subsequently, the MLCC is obtained by lamination, pressing, cutting, degreasing and co-firing in a reducing atmosphere, and then undergoing re-oxidation and outer electrode formation steps.

[0055] After co-firing, the resulting MLCC chip was sliced ​​and polished. The grain size of the dielectric layer was observed using a scanning electron microscope or a transmission electron microscope. The distribution of Ca, Zr, and Mn in the grain center, outer layer, and grain boundary regions was detected using energy dispersive spectroscopy (EDS) line scanning or area scanning of the transmission electron microscope. The results showed that the average grain size of the barium titanate-based grains in the dielectric layer was 0.10–0.35 μm, and the grains had outer regions enriched with Ca, Zr, and Mn.

[0056] (3) Preparation and performance testing of automotive-grade MLCCs Using the coated powder obtained in Example 3 as the main material, an aqueous ceramic slurry with a solid content of 65 wt% was prepared according to the above-mentioned aqueous slurry formulation and ball milling process. After casting, printing of nickel internal electrodes, stacking, pressing, cutting, and debinding, the slurry was co-fired in a reducing atmosphere and annealed in a weak oxidizing atmosphere to prepare automotive-grade MLCC samples with a dielectric layer sintering thickness of 0.3-0.8 μm.

[0057] The distribution of Ca, Zr, and Mn in the grain center, outer layer, and grain boundary regions was detected by scanning transmission electron microscopy (STEM) line scanning or area scanning on the cross-section of co-fired automotive-grade MLCCs. The results showed that Ca, Zr, and Mn elements were not uniformly distributed inside the grains, but were significantly enriched in the outer layer (shell) and grain boundary regions, forming a typical "core-shell" microstructure.

[0058] In automotive-grade MLCCs (such as those with AEC-Q200 certification), the dielectric layer must withstand extreme temperature shocks and high-voltage biases. If Ca, Zr, and Mn uniformly enter the crystal lattice, it will severely damage the ferroelectricity of BaTiO3, leading to a significant decrease in dielectric constant (capacitance). In this embodiment, ALD is used to coat the surface, and during sintering, the Kirkendall effect and grain boundary diffusion kinetics are utilized to allow these elements to naturally segregate and enrich in the grain boundaries and shell. The interior of the grain (core) maintains the high dielectric properties of high-purity BT (capacitance retention); while the grain boundaries and shell are enriched with Mn and Ca, forming a highly insulating, high-barrier grain boundary layer that acts like a firewall, blocking the migration of oxygen vacancies and electrons. This improves the high-temperature and high-humidity bias reliability of automotive-grade MLCCs without sacrificing capacity.

[0059] Automotive-grade reliability testing (THB): In accordance with the AEC-Q200 standard, the sample is subjected to high temperature and high humidity bias (THB) testing under conditions of 150°C, 95% RH, and twice the rated voltage (20V).

[0060] MLCCs made using the aforementioned dielectric powder meet the X7R or X8R temperature characteristics; after undergoing 1000 temperature cycles at -55~+125℃ or -55~+150℃, 85℃ / 85%RH / rated voltage / 1000 h of bias damp heat, and 125℃ or 150℃ / rated voltage / 1000 h of high-temperature service life tests, they show no cracks, delamination, breakdown, or short circuits, with a capacitance change rate not exceeding ±12.5%, and an IR×C of not less than 50 s at 25℃.

[0061] To illustrate the technical effects of the present invention, the following comparative examples were set up and compared using the same BT-based dielectric powder core, the same slurry system, the same casting thickness, and the same degreasing and co-firing process.

[0062] Comparative Example 1: No ALD coating treatment was performed on the BaTiO3 powder. The traditional mixed additive route was adopted, and Mg / Mn / rare earth additives were conventionally mixed in.

[0063] Comparative Example 2: BaTiO3 powder was subjected to a single-layer ALD coating treatment, and a single TiO2 dispersion stabilization / barrier layer was used to form a TiO2 nanolayer with a thickness of about 1.0 nm.

[0064] Comparative Example 3: BaTiO3 powder was subjected to a single-layer ALD coating treatment, using a single insulating layer to form an Al2O3 nanolayer with a thickness of approximately 1.0 nm.

[0065] Comparative Example 4: Using a liquid-phase multi-element coating route, Bi / Nb / Co-type wet oxides were used to coat BaTiO3 powder.

[0066] The pH drift and Ba content of the slurry were tested using the above comparative examples and embodiments. 2+ Dissolution, dispersion particle size, grain size after sintering, dielectric constant, dielectric loss, and insulation resistance retention rate after biasing at 85℃ / 85%RH were tested.

[0067] Test method: pH drift: The coated or uncoated BT-based media powder was dispersed in an aqueous medium with a pH of 6.5-7.5 to form a dispersion with a solid content of more than 50 wt%. The pH change was measured after standing at 25°C for 12 hours.

[0068] Ba 2+ Dissolution: Take the supernatant of the dispersion and measure the Ba element concentration by inductively coupled plasma atomic emission spectroscopy or inductively coupled plasma mass spectrometry.

[0069] Film thickness: The particle cross-section was observed using high-resolution transmission electron microscopy, and the equivalent thickness was calculated by combining X-ray photoelectron spectroscopy depth analysis and inductively coupled plasma elemental analysis.

[0070] Grain size and shell distribution: The co-fired MLCC chip was sliced ​​and polished. The grain size of the dielectric layer was observed by scanning electron microscopy or transmission electron microscopy. The distribution of Ca, Zr and Mn in the grain center, outer layer and grain boundary region was detected by scanning transmission electron microscopy line scanning or area scanning.

[0071] Reliability: The change in insulation resistance over time was tested under 85℃, 85%RH and set bias conditions, and the reliability was evaluated by the insulation resistance retention rate after the test.

[0072] The test results are shown in Table 1.

[0073] Table 1

[0074] The above predictive results indicate that uncoated BaTiO3 powder is prone to Ba oxidation in aqueous or alcohol-water systems. 2+ Dissolution and pH shift; a single TiO2 layer can improve Ba 2+While it can dissolve, its main function is to block and disperse, making it difficult to simultaneously provide grain boundary electrical regulation under a reducing atmosphere. Although a single Al2O3 layer can suppress sintering or grain growth, it may lead to the retention of non-ferroelectric insulating phases and insufficient retention of dielectric constant.

[0075] The Ca-Zr-Mn-O composite ALD nanolayer of the present invention can simultaneously provide surface chemical stability, Ca / Zr perovskite compatible outer layer formation and Mn grain boundary electrical modulation within a thickness range of sub-2 nm, thereby improving the reliability of thin dielectric layer MLCC while maintaining dielectric constant.

[0076] The Ca-Zr-Mn-O composite oxide nanolayer atomic layer deposition coating of BT-based dielectric powder of the present invention can be used for the preparation of ceramic slurries for MLCC dielectric layers, and is particularly suitable for high-capacity, miniaturized, thin dielectric layer, automotive-grade, and high-reliability MLCCs. This technology allows for adjustment of the Ca / Zr / Mn cycling ratio, film thickness, and slurry composition based on the BT-based powder particle size, dielectric material system, internal electrode material, and co-firing process, exhibiting good industrial applicability and process scale-up potential.

[0077] Although the above embodiments have described the present invention and its implementation in detail, it should be noted that for those skilled in the art, any changes, modifications, substitutions, combinations, simplifications, etc., made to the corresponding conditions without departing from the technical principles of the present invention should be considered as equivalent substitutions, and these improvements should also be considered within the scope of protection of the present invention.

Claims

1. A barium titanate dielectric powder coated with a composite oxide, characterized in that, The device includes a barium titanate dielectric powder core and a composite oxide nanolayer located on the surface of the barium titanate dielectric powder core; the barium titanate dielectric powder core is BaTiO3 or a barium titanate-based dielectric powder with BaTiO3 as the main crystalline phase; the composite oxide nanolayer is mainly composed of oxides of calcium, zirconium and manganese, and the composite oxide nanolayer is formed by atomic layer deposition (ALD) of powder, and the Ca, Zr and Mn elements are atomically distributed in the composite oxide nanolayer.

2. The barium titanate dielectric powder coated with composite oxide according to claim 1, characterized in that, The average particle size of the barium titanate dielectric powder core is 50-300 nm, and the specific surface area is 2-30 m². 2 / g; the equivalent thickness of the composite oxide nanolayer is 0.4-1.6nm.

3. The barium titanate dielectric powder coated with composite oxide according to claim 1, characterized in that, In the composite oxide nanolayer, the atomic ratio of Ca to Zr is 0.3:1 to 3:1, and the atomic percentage of Mn relative to the total amount of Ca, Zr and Mn is 0.5-12%.

4. The barium titanate dielectric powder coated with composite oxide according to claim 1, characterized in that, The core of the barium titanate dielectric powder is pure phase BaTiO3, or a barium titanate-based solid solution with BaTiO3 as the main crystalline phase and containing modifying elements; the modifying elements are selected from one or more of Ca, Sr, Zr, Hf, Sn, Mg, Mn or rare earth elements; wherein the core of the barium titanate dielectric powder contains at least one of BaTiO3, (Ba,Ca)TiO3, Ba(Ti,Zr)O3, Ba(Ti,Hf)O3, Ba(Ti,Sn)O3 or (Ba,Ca)(Ti,Zr)O3, and the mass percentage of the BaTiO3 main crystalline phase is not less than 80%.

5. The barium titanate dielectric powder coated with composite oxide according to claim 1, characterized in that, The composite oxide nanolayer is a multi-element composite oxide phase, which does not contain a continuous single compound phase composed of Ti, Al, Si, Li, F, or B elements; and based on the total number of atoms of the composite oxide nanolayer itself, the combined atomic percentage of the six impurity elements Ti, Al, Si, Li, F, and B is less than 10%; and the microstructure of the composite oxide nanolayer is selected from any of the following: (1) A nanolayered structure formed by alternating stacking of Ca-O sublayers, Zr-O sublayers and Mn-O sublayers; (2) The mixed layer structure in which Ca, Zr and Mn elements are uniformly distributed at the atomic level in the thickness direction; (3) A gradient layer structure with a concentration gradient, wherein the side closer to the core of the barium titanate dielectric powder is rich in Zr elements relative to the rest, and the side farther away from the core of the barium titanate dielectric powder is rich in Ca and Mn elements relative to the rest.

6. A method for preparing barium titanate dielectric powder coated with composite oxide, characterized in that, Using barium titanate dielectric powder as the core, the process includes the following steps: S1: The barium titanate dielectric powder is dried and surface activated; S2: Place the treated barium titanate dielectric powder into a powder atomic layer deposition reactor; S3: Perform a Zr-O deposition sub-cycle, including pulsed introduction of Zr source precursor into the reactor and purging, followed by pulsed introduction of oxygen source and purging; S4: Perform a Ca-O deposition sub-cycle, including pulsed introduction of Ca source precursor into the reactor and purging, followed by pulsed introduction of oxygen source and purging; S5: Perform a Mn-O deposition sub-cycle, including pulsed introduction of Mn source precursor into the reactor and purging, followed by pulsed introduction of oxygen source and purging; S6: Combining S3, S4 and S5 into a supercycle and repeating it to form the composite oxide nanolayer on the surface of barium titanate dielectric powder; Each supercycle includes 1-5 Zr-O deposition subcycles and 1-5 Ca-O deposition subcycles, and the ratio of the number of executions of the Zr-O deposition subcycle, Ca-O deposition subcycle and Mn-O deposition subcycle is (1-5): (1-5): (0.1-2); the powder atomic layer deposition temperature is 80-280℃.

7. The method for preparing composite oxide-coated barium titanate dielectric powder according to claim 6, characterized in that, The Zr source precursor is tetra(dimethylamino)zirconium, tetra(diethylamino)zirconium, tetra(ethylmethylamino)zirconium, tert-butoxide zirconium, or a combination thereof; the Ca source precursor is bis(trimethylsilyl)aminocalcium, dicyclopentadienylcalcium, a calcium β-diketone complex, or a combination thereof; the Mn source precursor is dicyclopentadienylmanganese, tris(2,2,6,6-tetramethyl-3,5-heptadecanoic acid)manganese, a manganese amidine complex, or a combination thereof; the oxygen source is H2O, O3, oxygen plasma, alcohol vapor, or a combination thereof. The powder atomic layer deposition reactor is a vibrating fluidized bed reactor, a rotating bed reactor, a pulsed fluidized bed reactor, an acoustically assisted fluidized bed reactor, or a stirred bed reactor. During the deposition process, the barium titanate media powder core is in a fluidized state or a tumbling and rotating state within the reactor.

8. A ceramic slurry, characterized in that, Includes barium titanate media powder coated with composite oxide as described in any one of claims 1-5, an organic carrier, a dispersant, and a solvent; The solvent is an aqueous solvent or an alcohol-water mixture; the solid mass percentage of the barium titanate dielectric powder coated with the composite oxide in the ceramic slurry is 45-80 wt%, and the mass percentage of the dispersant relative to the barium titanate dielectric powder coated with the composite oxide is ≤2.0 wt%.

9. A multilayer ceramic capacitor, comprising a ceramic body and external electrodes disposed at both ends of the ceramic body; the ceramic body comprising alternating layers of dielectric layers and internal electrode layers, characterized in that, At least one of the dielectric layers is prepared by casting, drying, laminating, degreasing and sintering in a reducing atmosphere from the ceramic slurry as described in claim 11, wherein the thickness of the dielectric layer after sintering is 0.3-2.0 μm and the average grain size of the barium titanate-based grains in the dielectric layer is 0.10-0.35 μm; The barium titanate-based grains have an outer region enriched with Ca, Zr and Mn and a central region that maintains the main crystalline phase of barium titanate, wherein the thickness of the outer region is 5-40 nm. The inner electrode layer comprises at least one of Ni, Ni alloy, Cu, or Cu alloy.

10. The multilayer ceramic capacitor according to claim 9, characterized in that, The temperature characteristics of the multilayer ceramic capacitor meet the EIA standard X5R, X7R or X8R.